Src family kinases engage differential pathways for encapsulation into extracellular vesicles - Chenming Ye; Cade Gosser; Ethan Daniel Runyon; Junyi Zha; Jingwen Cai; Zanna Beharry; Catherine Bowes Rickman; Mikael Klingeborn; Yutao Liu; Jin Xie; Houjian Cai (Journal of Extracellular Biology, 2023)
Abstract Extracellular vesicles (EVs) are heterogeneous biological nanoparticles secreted by all cell types. Identifying the proteins preferentially encapsulated in secreted EVs will help understand their heterogeneity. Src family kinases including Src and Fyn are a group of tyrosine kinases with fatty acylation modifications and/or multiple lysine residues (contributing charge interaction) at their N‐terminus. Here, we demonstrate that Src and Fyn kinases were preferentially encapsulated in EVs and fatty acylation including myristoylation and palmitoylation facilitated their encapsulation. Genetic loss or pharmacological inhibition of myristoylation suppressed Src and/or Fyn kinase levels in EVs. Similarly, loss of palmitoylation reduced Fyn levels in EVs. Additionally, mutation of lysine at sites 5, 7, and 9 of Src kinase also inhibited the encapsulation of myristoylated Src into EVs. Knockdown of TSG101, which is a protein involved in the endosomal sorting complexes required for transport (ESCRT) protein complex mediated EVs biogenesis and led to a reduction of Src levels in EVs. In contrast, filipin III treatment, which disturbed the lipid raft structure, reduced Fyn kinase levels, but not Src kinase levels in EVs. Finally, elevated levels of Src protein were detected in the serum EVs of host mice carrying constitutively active Src‐mediated prostate tumours in vivo. Collectively, the data suggest that different EVs biogenesis pathways exist and can regulate the encapsulation of specific proteins into EVs. This study provides an understanding of the EVs heterogeneity created by different EVs biogenesis pathways.